(untitled) (Olhar de Professor, 2020)
The political-pedagogical contributions of Paulo Freire are undeniable. Why is he then a thinker so contested by some segments of Brazilian society? The rise of an authoritarian thought in Brazil in the last few years puts under suspicion any pedagogical perspective that defines itself as emancipatory and formative of an emancipated individual, one who is capable of making decisions and is predisposed to dialogue with different interlocutors. The present paper focuses on the analysis of the emancipatory potential of freirian pedagogy, reason for which he is contested in such a violent way by defenders of authoritarian ideas. Looking to account for this problematic, the paper begins with a problematization of the challenges faced by an emancipatory pedagogy in the present context; makes a brief diagnosis about the authoritarian dimension in the contemporary society; recuperates fundamental elements in the emancipatory pedagogy of Freire and concludes reaffirming the thesis about the necessity of giving more visibility to freirian ideals in the formation of a subject who is critical, creative and emancipated, especially in the context of school education.